Concrete columns subjected to biaxial loadings - Heng, Tian Ming. (2012)
This report aims to study the behaviour of columns subjected to biaxial bending at ambient temperature. Experiments were conducted on three symmetrically reinforced concrete columns. The concrete columns were subjected to biaxial load eccentricities of 25, 40 and 60mm and they were tested to failure to obtain their ultimate strengths under biaxial bending. Subsequently, interaction diagrams were constructed based on the analytical expressions given in American Concrete Institute (ACI 318) and Eurocode-2 (EC-2). Second order effects were taken into account using the moment magnifier method and the nominal stiffness method. Simplified criteria including the Load Contour Method and Bresler’s Reciprocal Load method were used to obtain the biaxial failure loads conforming to the design codes. Critical parameters influencing the column capacity were evaluated and discussed. This includes variables such as the effective creep ratio, geometric imperfections, concrete cover and strength reduction factors. Test results were also compared with theoretical development and numerical simulations. This enables the capacity of the columns to be verified and ensure that the data obtained were accurate to a sufficient degree for uses in professional practice and future works.